Desempeño laboral de los asesores de ventas de la empresa automores y anexos Nissan y Renault de la ciudad de Guayaquil - Muñoz Bajaña, Solange Stefanía (2020)
Motivation in the staff is significant within any company since it provides that they are always energetic and willing to carry out the tasks with greater efficiency, being motivated generates in the workers a sense of relevance, as well as the integration of ideas presented by practitioners generates satisfaction. Managers must take into account that in order to achieve the organizational objectives, the collaborations of their employees must be considered. This study aims to reveal the different reasons for lack of motivation that appear in the sales advisors of the company Automotores y Anexos Nissan and Renault Since one of the most significant problems that exists within many institutions is undoubtedly motivational dismissal, this means that employees do not carry out their tasks effectively, directly affecting or delaying the institution's productivity.